Mobile application for the aging population - Phui, Jing Yun (2017)
The world’s older population continues to grow at a remarkable rate. Today, 8.5 percent of people worldwide (approximately 630 million) are aged 65 and over. The increase in our aging population presents several public health challenges as well as many opportunities that we need to be ready for. We are witnessing population aging in every parts of the world, not only Singapore. This project aims to develop a mobile application that suit the needs of the older generation. It enhances their interaction with a mobile application and has the interface designed specifically for them. This report outlines the design and development process of the application. Main programming languages used in the project are HTML, CSS, Ionic framework and AngularJS. Google Map API and Google Translate API makes the idea of this project possible. This application is specially designed to cater to the needs of the elderly. This project has taken into consideration the user interface design and practical usage of mobile application for the aging population. It is specially design to have simple application structure and navigation, such that users will be able to access the application’s function with no more than three clicks. Thus, increase user satisfaction rate and enhance user experience.